Perfil de metilação de genes de reparo de fita dupla de DNA e sua correlação com a expressão gênica em pacientes com Síndrome Mielodisplásica e agricultores expostos a agrotóxicos - Monte, Cristiane da Silva (2021)
Myelodysplastic syndromes (MDS) constitute a heterogeneous group of clonal hematopoietic diseases with aberrant methylation patterns described for some genes, being one of the most studied epigenetic mechanisms in the pathophysiology of the disease and its influence on prognosis. Exposure to pesticides is one of the predisposing factors to MDS, as these substances can induce dysregulation in the expression of repair genes, chromosomal abnormalities and alterations in epigenetic mechanisms, including methylation. This work evaluated the methylation profile of genes acting in the DNA double-stranded repair mechanism (ATM, BRCA1, BRCA2, LIG4 and RAD51) and its relationship with gene expression in samples from MDS patients, from farmers exposed to pesticides and from controls without the disease. For this investigation, the pyrosequencing technique was used, which provides quantitative data on methylation at CpG sites. In the analysis of methylation in MDS patients, the ATM gene was the only one that showed significant results, with higher methylation in males (p = 0.037), in patients aged up to 60 years (p = 0.002) and in those who progressed to AML (p = 0.016). When comparing the methylation between the groups of exposed farmers, SMD advanced forms and controls, we detected significant differences, with levels always being higher in the control group: ATM (p=0.037; control group x farmers p= 0.000), BRCA1 (p= 0.001; exposed x control group, p=0.001; MDS x control, p=0.001;), BRCA2 (p=0.006; farmers x control, p=0.027; MDS x control, p=0.004), LIG4 (p=0.009; farmers x control, p=0.001; MDS x control, p=0.012) and RAD51 (p=0.009; farmers x controls, p=0.047). The methylation analysis between groups of unexposed farmers, low-risk MDS and controls also showed higher levels of methylation in the control group, with significant differences for the BRCA1 genes (p=0.001; farmers x controls, p=0.001) BRCA2 (p=0.004; MDS x controls, p=0.004; farmers x controls, p=0.014) and LIG4 (p=0.001, in MDS x controls and farmers x controls). The correlation analysis between methylation and expression showed a positive and strong correlation for LIG4 gene in the Advanced Forms MDS group (p=0.006; ⍴=0.798) and a positive and weak correlation for BRCA1 gene in the exposed farmers group (p= 0.046; ⍴=0.340). This study corroborates the phenomenon of hypermethylation in some DNA repair genes in Myelodysplastic Syndrome and suggests a significant reduction in methylation in farmers exposed to pesticides.